MEASURING KEY DETERMINANT FACTORS OF RESPONSIBLE ENVIRONMENTAL BEHAVIOR AMONG SECONDARY PUBLIC SCHOOLS IN PUTRAJAYA, MALAYSIA - Amin Sarman; Fazilah Razali (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The environment is very important to sustain the prosperity of the nation, society, and human beings. Negligence to protect the environment will result in great catastrophes by causing natural disasters to plague mankind. Environmental education has been regarded as a strategic solution to overcome challenging environmental issues. there is no specific subject on environmental education in the Malaysian school syllabus which led to poor public awareness, lack of understanding, and exposure to environmental issues and knowledge. Hence, this study is conducted to measure the level of environmental literacy among secondary school students in Putrajaya, Malaysia. Descriptive research design and correlation were used in this study. Instruments for Environmental Attitude Inventory (EAI) comprises a scale of 1-5 ranging from strongly agree to strongly disagree and was distributed to 120 from four students who were selected using simple random sampling. The finding shows that the value of the Adjusted R square is 0.260, which indicates that the factor-independent variables (knowledge, beliefs, and attitudes) only contributed to 26% of the influencing dependent variable (responsible environmental behavior). This value is more appropriate for determining the actual value in a population with a small sample size. Coefficients multiple linear regressions show that the value of t=0.358 shows knowledge does not influence responsible behavior while the most dominant is attitude. It is hoped that the findings from this research will contribute to environmental education in Malaysia.